2011
DOI: 10.1590/s0103-21002011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção educativa para o autocuidado de indíviduos com diabetes mellitus

Abstract: OBJETIVO: Analisar conhecimentos, atitudes e práticas do autocuidado de indivíduos com Diabetes mellitus (DM) em um serviço especializado de saúde de Belo Horizonte - MG, Brasil. MÉTODOS: Pesquisa do tipo estudo de caso com abordagem qualitativa. Os dados foram coletados por meio da realização de grupos focais com participação de 12 indivíduos com DM e que compareceram em três sessões do programa educativo desenvolvido nesse serviço de saúde. RESULTADOS: Os dados, analisados segundo o enfoque da análise temáti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
20

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
2
10
0
20
Order By: Relevance
“…The sociodemographic characteristics of individuals participating in the study are similar to other studies of individuals with DM, as age over 60 years; (21,22) most female, (22) with a partner (23) , low level of education, (22) retired (23) and an income above the minimum salary. (22) In the second phase of the study, there was an increase of postprandial blood glucose and blood pressure in the control group and showed statistically significant reduction in HbA1c in both groups, as well as fasting glucose and DBP in EG.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The sociodemographic characteristics of individuals participating in the study are similar to other studies of individuals with DM, as age over 60 years; (21,22) most female, (22) with a partner (23) , low level of education, (22) retired (23) and an income above the minimum salary. (22) In the second phase of the study, there was an increase of postprandial blood glucose and blood pressure in the control group and showed statistically significant reduction in HbA1c in both groups, as well as fasting glucose and DBP in EG.…”
Section: Discussionsupporting
confidence: 55%
“…(23,25) The acquisition of knowledge about the dis-ease among individuals with DM is important, given the chronicity of the disease and need for skills development to promote self-care of individuals. (22) Although there has been a significant increase in knowledge in EG after participation in the program, the participants in this group had a slight increase in attitude scores. The DM is a chronic disease whose treatment requires major changes in lifestyle, (2) as well as potential factors for chronic complications, all of which can interfere with coping with the disease.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Torres et al 12 consideram significativa a relação entre a prática do autocuidado e a melhoria da qualidade de vida. Assim, um dos fatores a serem considerados na assistência à saúde é a promoção do conhecimento aos portadores de doenças crônicas, considerando que são responsáveis, dentro de suas limitações, de seu próprio autocuidado e de seu bem-estar.…”
Section: Resultsunclassified
“…Authors concluded that this type of strategy is an inexpensive and effective tool that can be used by the team to assist adolescents in managing diabetes and their daily lives. Continuing education provided by professionals committed to the promotion and maintenance of care and self-care may contribute to healthy living and to improving QoL of diabetics 40 . A different approach was used in a study 4 that aimed to evaluate glycemic control, weight status and quality of life over 12 months of adolescents with type 1 diabetes.…”
Section: Resources Used To Help Adolescents In the Management Of Diabmentioning
confidence: 99%